Diallyl-n-Sulfide of Garlic Inhibits Glycogenolysis in Heat-Stressed Laying Sentul Chicken - A. Mushawwir; D. Latipudin; R. Permana; N. Suwarno (Jurnal Sain Peternakan Indonesia, 2021)
Heat stress causes a decrease in metabolic function and immunity, which results in a decrease in production. The provision of natural extracts such as the active compound dyally n-suldifa (Dn-S) is one strategy to overcome the adverse effects of heat stress. One hundred and twenty-five female laying native chickens, with an average body weight of 1213.83±15.52 g, 40 weeks old, were used in this experiment, to study the impact of Dn-S administration from garlic on the metabolite profile of the glycogenolysis pathway. laying. Laying hens were distributed into five treatment groups, each with 25 samples. Dn-S isolation from garlic isolated by distillation technique. The study was carried out with five types of experimental treatments, as follows the group with a comfort zone temperature (24°C) and without the administration of Diallyl n-Sulfide (Dn-S), heat stress (38°C) and without Dn-S, heat stress (38°C) and 100 µL Dn-S, heat stress (38°C) and 125 µL Dn-S, heat stress (38°C) and 150 µL Dn-S/head. Based on the results of the study, it was shown that heat stress causes an increase in the rate of glycogenolysis and intermediate metabolites and their catalyzing enzymes. It appears that the administration of 150 µL Dn-S, effectively reduces the rate of glycogenolysis. It was concluded that heat stress on laying hens could be avoid by administering garlic Dn-S.